Evaluation of microstructure and mechanical property variations in AlxCoCrFeNi high entropy alloys produced by a high-throughput laser deposition method. (April 2018) - Li, Mu; Gazquez, Jaume; Borisevich, Albina; Mishra, Rohan; Flores, Katharine M.
Abstract: Twenty-one distinct Alx CoCrFeNi alloys were rapidly prepared by laser alloying an equiatomic CoCrFeNi substrate with Al powder to create an alloy library ranging x = 0.15–1.32. Variations in crystal structure, microstructure and mechanical properties were investigated using X-ray diffraction, scanning electron microscopy, scanning transmission electron microscopy and nanoindentation. With increasing Al content, the crystal structure transitioned from a disordered FCC to a mixture of disordered BCC and ordered B2 structures. While the onset of BCC/B2 formation was consistent with previously reported cast alloys, the FCC structure was observed at larger Al contents in the laser processed materials, resulting in a wider two phase regime. The FCC phase was primarily confined to the BCC/B2 grain boundaries at these high Al contents. The nanoindentation modulus and hardness of the FCC phase increased with Al content, while the properties of the BCC/B2 structure were insensitive to composition. The structure and mechanical properties of the laser-processed alloys were surprisingly consistent with reported results for cast alloys, demonstrating the feasibility of applying this high-throughput methodology to multicomponent alloy design. Highlights: A high-throughput laser deposition-basedtechnique for fabricating high-entropy alloys is proposed. Microstructural and mechanical property variations can be characterized in a non-destructive manner. Remarkable consistency between the cast and laser-processed microstructures and properties over a wide compositional range isobserved.